2021
DOI: 10.1159/000520903
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sodium-Glucose Cotransporter 2 on Amputation Events: A Systematic Review and Meta-Analysis of Randomized-Controlled Trials

Abstract: <b><i>Introduction:</i></b> Sodium-glucose cotransporter 2 (SGLT2) inhibitors are increasingly utilized in the treatment of diabetes mellitus as well as therapeutic extra-glycemic effects. However, there are still concerns over complications such as amputation events, given the results from the Canagliflozin Cardiovascular Assessment Study (CANVAS) trial. Hence, we conducted a systematic review and meta-analysis of randomized-controlled trials to investigate the effect of SGLT2 inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
4
0
3
Order By: Relevance
“…There were no obvious differences in amputation events by type of SGLT2 inhibitor, by baseline population, and by duration of SGLT2 inhibitor use [ 148 ].…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…There were no obvious differences in amputation events by type of SGLT2 inhibitor, by baseline population, and by duration of SGLT2 inhibitor use [ 148 ].…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…People living with diabetes are inherently at elevated risk for LLA events [87,96,97]. Excess amputations were reported in one CVOT and were not replicated across subsequent trials [17,18,21,28,53,98,99]. Everyone with T2DM should be educated regarding the importance of preventative foot care and regular comprehensive assessment of lower limbs must be included in clinical reviews [8,87,96,100].…”
Section: A Step-change In T2dm Management: Bridging the Gap Between G...mentioning
confidence: 99%
“…[ 1 4 , 8 , 9 , 11 , 12 , 17 40 , 49 , 51 , 53 56 , 61 – 66 , 68 75 , 83 , 84 , 87 – 89 , 98 110 , 121 , 127 130 ]…”
unclassified
“…The higher risk of limb amputations reported in the CANVAS study [ 5 ] raised concern. However, most large studies did not find an increased risk and a recent meta-analysis confirmed no increase in amputations in a combined cohort of 63,716 patients [ 151 ]. This evidence was consistent across different types of SGLT2 inhibitors, baseline populations and lengths of treatment use.…”
Section: Adverse Effectsmentioning
confidence: 99%